Kebijakan pengelolaan arsip perguruan tinggi Islam di era industri 4.0 (studi pada Record Center Institut Agama Islam Negeri Curup) - Rhoni Rodin; Khusnul Khotimah; Moga Perdana; Ricca Dwi Mahfiro (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2022)
The purpose of this study was to analyze the archive management policy of the Curup State Islamic Institute (IAIN) in the industrial era 4.0. This type of research is descriptive with a qualitative approach. Data collection techniques were carried out by interview, observation and documentation methods. The results showed that the management of archives at the IAIN Curup record center had not implemented the standards contained in the Regulation of the Head of ANRI No. 31 of 2015 concerning the guidelines for the establishment of the Archives Depot, so that the Archives would continue to make improvements to both the leading sectors of the organizational structure, funding, facilities and human resources. Therefore, there are several strategies carried out by the IAIN Curup archive manager in the 4.0 era, namely 1) a management policy in the field of organizational structure, an organizational structure and standard operating procedure (SOP) will be made so that archival activities can run in a professional, structured manner. and measurable; 2) the policy in the field of funding, of course, will increase the funds for the management of records that require funds; 3) the policy in the field of facilities, efforts will be made to improve archival facilities and facilities such as computers, additional archive racks, and other infrastructure facilities; 4) policy in the field of human resources, efforts will be made to increase archival human resources either through formation or participating in training activities; and 5) policy in the field of archival systems and applications, efforts will be made to implement archival systems and applications, and increase human resources who understand information technology.